Modeling of synchronous generator - Feng, Daixin (2015)
Developing electrically-powered systems to boost the performance and reliability of tomorrow’s aircraft is one of the major challenges facing the aircraft industry. The innovative technologies applied in MEA(more electric aircraft)will deliver ahost of advantages starting with higher reliability than today’s hydraulic and pneumatic systems. They also save weight, since different systems can share the same computers and electronics. Lower weight translates into reduced fuel burn and greater payload capacity. At the same time, energy consumption is reduced by more carefully controlling the allocation of resources. And the maintenance costs are cut and dispatch reliability is increased because electrical systems are faster and easier to repair. The increasing electrical power consumptions on MEA indicate a higher demand on generators.In thisproject, the practical options of synchronous generator willbe studied by making amathematicalmodel and analyzing the simulation result.